Glutaraldehyde-crosslinked chitosan-polyethylene oxide nanofibers as a potential gastroretentive delivery system of nizatidine for augmented gastroprotective activity - Walaa Ebrahim Abd El Hady; Osama Abd El-Aazeem Soliman; Hassan Mohamed El Sabbagh; Elham Abdelmonem Mohamed (Taylor & Francis Group, 2021)
Nizatidine (NIZ), a histamine H2-receptor antagonist, is soluble and stable in the stomach, however, it exhibits a short half-life and a rapid clearance. Therefore, chitosan (CS) and polyethylene oxide (PEO) nanofibers (NFs) at different weight ratios were prepared by electrospinning and characterized. The selected uncrosslinked and glutaraldehyde-crosslinked NFs were investigated regarding floating, solid-state characteristics, in vitro release, and in vitro cytotoxicity. The cytoprotective activity against ethanol-induced gastric injury in rats was evaluated through macroscopical, histopathological, immunohistochemical, and oxidative stress examinations. NFs based on 8:2 CS:PEO exhibited the smallest diameter (119.17 ± 22.05 nm) and the greatest mucoadhesion (22.82 ± 3.21 g/cm2), so they were crosslinked with glutaraldehyde. Solid-state characterization indicated polymers interaction, a successful crosslinking, and NIZ dispersion in NFs. Crosslinking maintained swollen mats at pH 1.2 (swelling% = 29.47 ± 3.50% at 24 h), retarded their erosion at pH 6.8 (swelling%= 84.64 ± 4.91% vs. 25.40 ± 0.79% for the uncrosslinked NFs at 24 h), augmented the floating up to 24 h vs. 10 min for the uncrosslinked NFs at pH 1.2 and prolonged the drug release (%drug released ≥ 93% at 24 h vs. 4 and 5 h for the uncrosslinked NFs at pHs 1.2 and 6.8, respectively). The viability of Caco-2 cells ≥ 86.87 ± 6.86% revealed NFs biocompatibility and unreacted glutaraldehyde removal. Crosslinking of 8:2 CS:PEO NFs potentiated the antiulcer activity (38.98 vs. 8.67 for the uncrosslinked NFs) as well as it preserved the gastric wall architecture, COX-2 expression, and oxidative stress markers levels of the normal rats.